Rates of admission for ambulatory care sensitive conditions in France in 2009–2010: trends, geographic variation, costs, and an international comparison - Weeks, Bill; Ventelou, Bruno; Paraponaris, Alain (European Journal of Health Economics, 2016)
Abstract Background Admissions for ambulatory care sensitive conditions (ACSCs) are considered preventable and indicators of poor access to primary care. We wondered whether per-capita rates of admission for ACSCs in France demonstrated geographic variation, were changing, were related to other independent variables, or were comparable to those in other countries; further, we wanted to quantify the resources such admissions consume. Methods We calculated per-capita rates of admission for five categories (chronic, acute, vaccination preventable, alcohol-related, and other) of ACSCs in 94 departments in mainland France in 2009 and 2010, examined measures and causes of geographic variation in those rates, computed the costs of those admissions, and compared rates of admission for ACSCs in France to those in several other countries. Results The highest ACSC admission rates generally occurred in the young and the old, but rates varied across French regions. Over the 2-year period, rates of most categories of ACSCs increased; higher ACSC admission rates were associated with lower incomes and a higher supply of hospital beds. We found that the local supply of general practitioners was inversely associated with rates of chronic and total ACSC admission rates, but that this relationship disappeared if we accounted for patients’ use of general practitioners in neighboring departments. ACSC admissions cost 4.755 billion euros in 2009 and 5.066 billion euros in 2010; they consumed 7.86 and 8.74 million bed days of care, respectively. France had higher rates of ACSC admissions than most other countries examined. Conclusions Because admissions for ACSCs are generally considered a failure of outpatient care, cost French taxpayers substantial monetary and hospital resources, and appear to occur more frequently in France than in other countries, policymakers should prioritize targeted efforts to reduce them.